Anti-Ro52 antibody level is an important marker of fetal congenital heart block risk in anti-Ro/SSA antibody positive pregnancy. Issue 4 (4th July 2018) - Miyasato-Isoda, Mai; Waguri, Masako; Yamada, Yuko; Miyano, Akira; Wada, Yoshinao
Abstract: Objective: The aims of this study are to determine the incidence of congenital heart block (CHB) in the Japanese population and identify maternal factors predicting fetal CHB in anti-Ro/SSA antibody positive pregnancy. Methods: A retrospective study was performed using 52, 147 clinical records of pregnancies followed in a single center. For 183 anti-Ro/SSA antibody-positive women, anti-Ro52 and Ro60 antibodies were measured, and the odds of CHB in relation to maternal clinical features were calculated by multivariate analysis. The receiver-operating characteristic (ROC) curves for predicting CHB were constructed for the titers of anti-Ro/SSA, anti-Ro52 and anti-Ro60 antibodies. Results: Fetal CHB occurred in two pregnancies among those without known risks such as positive anti-Ro/SSA antibody or previous CHB-affected pregnancy, suggesting an incidence similar to that in Caucasian populations. As for the anti-Ro/SSA antibody positive pregnancies, the titers of anti-Ro/SSA, anti-Ro52 and anti-Ro60 antibodies were independent risk factors for fetal CHB and the use of corticosteroids before 18 gestational weeks was an independent protective factor. The area under the ROC was 0.84, 0.73 and 0.74 for anti-Ro52, anti-Ro60 and anti-Ro/SSA antibodies, respectively. Conclusion: CHB occurred in two among approximately 50, 000 pregnancies without known risks such as positive anti-Ro/SSA antibody or previous delivery of CHB-affected babies. Measurement of anti-Ro52 antibody levels may be helpful in extracting a risk group of delivering CHB infants in the anti-Ro/SSA antibody positive pregnancy.